2016
DOI: 10.1155/2016/1370148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aerobic Exercise Training on Blood Pressure in Indians: Systematic Review

Abstract: Introduction. High blood pressure (BP) is one of the most important modifiable risk factors for cardiovascular diseases, which accounts for one in every eight deaths worldwide. It has been predicted that, by 2020, there would be 111% increase in cardiovascular deaths in India. Aerobic exercise in the form of brisk walking, jogging, running, and cycling would result in reduction in BP. Many meta-analytical studies from western world confirm this. However, there is no such review from Indian subcontinent. Object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 30 publications
3
18
0
3
Order By: Relevance
“…Por ejemplo, Punia y cols 17 , en una revisión sistemática de los estudios realizados en india en pacientes con Hta tratados con medicamentos antihipertensivos lograron -3 a -6 mmHg. nemoto y cols 18 produjeron una reducción máxima de -10 mmHg en el grupo de caminata a elevada intensidad, al igual que gunjal y cols 19 , quienes obtuvieron disminuciones promedio de -4,5 mmHg.…”
Section: Discussionunclassified
“…Por ejemplo, Punia y cols 17 , en una revisión sistemática de los estudios realizados en india en pacientes con Hta tratados con medicamentos antihipertensivos lograron -3 a -6 mmHg. nemoto y cols 18 produjeron una reducción máxima de -10 mmHg en el grupo de caminata a elevada intensidad, al igual que gunjal y cols 19 , quienes obtuvieron disminuciones promedio de -4,5 mmHg.…”
Section: Discussionunclassified
“…In addition, no significant difference was denoted in the blood pressure and body weight between the experimental and control groups. According to the findings, aerobic exercises may be effective in the treatment of mild hypertension in India [23]. Li et al (2008) performed a cross-sectional research in Tushala (China) and 28 surrounding villages using stratified random sampling.…”
Section: Resultsmentioning
confidence: 99%
“…However, there was no significant difference between a combination of these two interventions and each intervention alone in controlling blood pressure. Numerous studies have reported decreased blood pressure following regular exercise (23,24) or garlic supplement consumption (25).…”
Section: Discussionmentioning
confidence: 99%